Effect of scarlet fever toxin on the phagocytic activity of the reticuloendothelial system - Hríbalová, V (Folia microbiologica, 1979)
In normal rabbits and mice, one i.v. injection of scarlet fever toxin (ET) (30 000 STD per kg of rabbit weight or 20-g mouse) elicited a similar biphasic change in carbon clearance rate - early depression followed by a stimulating phase - as has been described for Gram-negative endotoxins. Prolonged depression without a subsequent stimulation phase was obtained in mice by raising the ET dose. The reasons of the discrepancy between these findings and those of Hanna and Watson (1965b) are discussed. Pyrogenic tolerance to ET is not accompanied by accelerated carbon clearance and is not impaired by RES blockade. A possible mechanism of ET tolerance is suggested.
Keywords: Mononuclear Phagocyte System; oxid thoričitý; Colloids; Fever; Male; Exotoxins; Streptococcus pyogenes; koloidy; uhlík; fagocytóza; Escherichia coli; mužské pohlaví; králíci; exotoxiny; mononukleární fagocytární systém; Scarlet Fever; Animals; horečka; Metabolic Clearance Rate; ženské pohlaví; Salmonella paratyphi B; zvířata; Carbon; Rabbits; myši; Phagocytosis; Bacterial Toxins; spála; Endotoxins; Mice; endotoxiny; Female; metabolická clearance; Thorium Dioxide; bakteriální toxiny